Comparative study of the chemical kinetics of two catalysts used for esterification of sludge palm oil - Hayyan, Adeeb; Mirghani, Mohamed Elwathig Saeed; Alam, Md. Zahangir; Kabbashi, Nassereldeen Ahmed; Mohd Hakimi, Noor Irma Nazashida; Mohd Siran, Yosri; Tahiruddin, Shawaluddin (2011)
Chemical kinetics study was carried out for batch esterification process. Reactant concentration (FFA) as function of time was plotted according to first and second order equations in order to study the catalytic activities of both toluene-4-sulfonic monohydrate acid (PTSA) and sulfuric acid. Pretreatment of Sludge Palm Oil (SPO) by esterification reaction was found to be a second order reaction. Sulfuric acid showed higher catalytic activity than PTSA. The rate constant K of using PTSA was 0.9 * 10-3 min-1 while K of using sulfuric acid was 2* 10-3 min-1.